English in the southern United States - Nagle, Stephen J., 1948-; Sanders, Sara L. (Studies in English language., 2003)
This volume, written by a team of experts, many of them internationally known, provides a broad overview of the foundations of and current research on language variation in the southern United States. Central themes, issues and topics of scholarly investigation and debate figure prominently throughout the volume.